A Novel Case of Penile Gangrene in a Patient Treated with Ibrutinib for Chronic Lymphocytic Leukemia. (23rd November 2016) - Skelton IV, William Paul; Akhavan, Neeka N.; Taylor, Zachary A.; Nguyen, Thu-Cuc; Hassan, Hassan; Townsend, Tabitha N.; Pathak, Prajwol; Trikha, Gaurav; Dang, Nam H.; Dang, Long H.; Ali, Azka
Abstract : Introduction . Ibrutinib is commonly used for the treatment of patients with CLL in either first-line or relapsed/refractory settings. Case Presentation . We present the case of a 74-year-old Caucasian man with CLL who presented with penile gangrene upon initiation of ibrutinib treatment. Our case is the first showing the complication of penile gangrene associated with ibrutinib use. The gangrene was self-limited upon discontinuing ibrutinib. Conclusion . Our finding describes a very rare yet important adverse event associated with ibrutinib use.